Critérios de seleção e utilização do livro didático de inglês na rede estadual de ensino de Goiás: um estudo de caso com quatro professoras - COSTA, Bianca Ribeiro Morais (2012)
The aim of this study is to point out the selection criteria and evaluation of English textbook in state schools of Goiás, considering the suggestions made by the Programa Nacional do Livro Didático (PNLD/2011), and the subsequent use of the adopted textbook in the classroom. The research, which follows the parameters of the qualitative approach, can be classified as a case study and was conducted in 2011 in the city of Anápolis, Goiás, where the researcher and the participants in this study live. Data were collected by means of questionnaires, interviews, audio recordings of classes and the researcher s field notes. The theoretical basis of this study is related to the context of teaching English in public schools (COX; ASSIS- PETERSON 2008; PAIVA, 2003; WALKER, 2003), the general characteristics of textbooks and their use in public schools (ALMEIDA FILHO; CONSOLO, 1990; RAMOS, 2009; MAGNO and SILVA, 2009), the specific characteristics of English book (ANSARY; BABAAI, 2002; XAVIER; SOUZA, 2008; TOMLINSON, 2008), the relationship between textbook and teaching practice (CORACINI , 1996; PEREIRA, 2007; SILVA, 1996), the selection criteria and evaluation of English textbook (DIAS, 2009, BROWN & RODGERS, 2002; RIBEIRO, 2008) and the implementation of the Programa Nacional do Livro Didático - PNLD/2011 in relation to the curriculum component: Modern Foreign Language - English and Spanish (BRASIL, 2010, BRASIL, 2011). The analysis results show that the English textbooks, in most cases, were selected based on the criteria suggested by the Programa Nacional do Livro Didático Língua Estrangeira Moderna (BRASIL, 2010) or by other criteria considered relevant by the teachers who made the choice. Regarding the use of the adopted textbook, we can see that this teaching material contributes to English teaching learning process, therefore, helping teachers and students in their activities, despite some negative features pointed out by the participants.